(3EOGQI GddhGRes - (3eMeO MjOQ UGOb(B, (3eMjdGfs ((3YeGf(B:s (3OGQ UaGA ddfTQ(B,s, 2002)
(3EOGQI GdehGO hGddhGRe, hUhd GdehGO hJObjbgG hGSJjdGegG, UQa GdehGO, JhQjO GdehGO ef GdeSJhOY GdaQYj, JOhjQ GdehGO, TWH GdehGO, efGhdI GdehGO, JWHjbGJ YedjIs
Keywords: (3GdehGO(B- (3GOGQIs